Colocalization of Mating-Induced Fos and D2-Like Dopamine Receptors in the Medial Preoptic Area: Influence of Sexual Experience - Nutsch, Victoria L.; Will, Ryan G.; Robison, Christopher L.; Martz, Julia R.; Tobiansky, Daniel J.; Dominguez, Juan M. (Frontiers in Behavioral Neuroscience, 2016)
Dopamine in the medial preoptic area (mPOA) stimulates sexual activity in males. This is evidenced by microdialysis and microinjection experiments revealing that dopamine receptor antagonists in the mPOA inhibit sexual activity, whereas agonists facilitate behavior. Microdialysis experiments similarly show a facilitative role for dopamine, as levels of dopamine in the mPOA increase with mating. While the majority of evidence suggests an important role for dopamine receptors in the mPOA in the regulation of male sexual behaviors, whether sexual activity or sexual experience influence dopamine receptor function in the mPOA has not been previously shown. Here, we used immunohistochemical assays to determine whether varying levels of sexual activity or experience influence the number of cells containing Fos or D2 receptor immunoreactivity. Results show that sexual experience facilitated subsequent behavior, namely experience decreased latencies. Moreover, the number of cells with immunoreactivity for Fos or D2 correlated with levels of sexual experience and sexual activity. Sexual activity increased Fos immunoreactivity. Sexually experienced animals also had significantly more D2-positive cells. Sexually inexperienced animals copulating for the first time had a larger percentage of D2-positive cells containing Fos, when compared to sexually experienced animals. Finally, regardless of experience, animals that had sex prior to sacrifice had significantly more D2-positive cells that contained Fos, versus animals that did not copulate. These findings are noteworthy because sexually experienced animals display increased sexual efficiency. The differences in activation of D2 and changes in receptor density may play a role in this efficiency and other behavioral changes across sexual experience.